Criminal-states and criminal-soldiers - Bunker, Robert J. (Routledge, 2008)
Looks at the theoretical and legal side of criminal-state and criminal-soldier emergence and growth. This book focuses on Al Qaeda, Hizballah, Mara Salvatrucha (MS 13), Caliphate and Mahdi concerns, Islamic Fundamentalist Use of Beheadings, Criminalization of Russian State Security, Nuclear Materials Trafficking, and Outlaw Private Security Firms.